2003
DOI: 10.1007/bf03325021
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and eating disorders: An examination of a day treatment program

Abstract: With shortened inpatient (IP) hospitalizations, DTPs can provide the long-term care required by many adolescent patients for psychological and physical recovery. This may be particularly important for the development of children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 12 publications
0
25
2
2
Order By: Relevance
“…The mean weight gain for the group as a whole was approximately 1 pound per week. The LOS for the patients in this study is less than that described for other day programs in the literature [1 -3] , with one review article of 6 day programs showing an LOS that ranged from a low of 4 -5 weeks to a high of 26 -39 weeks (4) , and a previous day program at our own institution showing a mean LOS of 10 -11 weeks (6,7) . Those day programs that have reported mean weight gain in the literature have generally reported 1 -2 pounds per week, with one program reporting a mean weight loss.…”
Section: Discussioncontrasting
confidence: 68%
“…The mean weight gain for the group as a whole was approximately 1 pound per week. The LOS for the patients in this study is less than that described for other day programs in the literature [1 -3] , with one review article of 6 day programs showing an LOS that ranged from a low of 4 -5 weeks to a high of 26 -39 weeks (4) , and a previous day program at our own institution showing a mean LOS of 10 -11 weeks (6,7) . Those day programs that have reported mean weight gain in the literature have generally reported 1 -2 pounds per week, with one program reporting a mean weight loss.…”
Section: Discussioncontrasting
confidence: 68%
“…A comparison between the PHP and residential programmes, using two‐tailed t ‐tests, revealed no significant differences in initial sample number ( t = 0.44, p = 0.66), discharge number ( t = 0.12, p = 0.90), per cent with discharge data ( t = 0.83, p = 0.42), age ( t = 0.52, p = 0.61) or duration of treatment ( t = 1.76, p = 0.09). For PHP, all but one study (Dancyger et al, ) reported a significant improvement in weight and/or ED behaviour at time of discharge. All residential programmes reported an improvement in weight and/or behaviour at time of discharge.…”
Section: Resultsmentioning
confidence: 97%
“…113 Still, short-term outcomes have generally been reported to be good. 110,113,114 A recent study that used a range of outcome measures, including BMI and measurement of binge-purge behavior, demonstrated day treatment to be highly effective in the treatment of both restrictive and binge-purge AN and BN. Furthermore, these results were sustained or improved over 18 months of follow-up.…”
Section: Day-treatment Programsmentioning
confidence: 99%